Hubungan Tingkat Stres dengan Kecenderungan Gangguan Makan pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - I Gusti Made Arya Janardana Kepakisan; Putu Asih Primatanti; Anak Agung Gede Indraningrat (Aesculapius Medical Journal, 2024)
[The Relationship between Stress Levels and Eating Disorder Tendencies in Students at the Faculty of Medicine and Health Sciences, Warmadewa University] Stress is the body's response towards changes that caused regulatory response, physical, psychological and emotional adaptation. In students, particularly medical students who are categorized in the young adult age group, stress often occurs due to internal and external factors. Stress was thought to cause eating disorder. Eating disorder could cause pressures to one's life, and as such could present a serious health problem to a person. The purpose of this study was to determine the relationship between stress level and the tendency of eating disorder in medical students of Faculty of Medicine and Health Sciences Warmadewa University. One hundreds and twenty four respondents were selected using simple random sampling and met inclusion and exclusion criteria. Information from respondents were obtained by sending questionnaires online. Data obtained from this study was analysed statistically using univariate and bivariate methods. Bivariate analysis were performed using Kruskal-Wallis test with Î±<0.05. Among 124 respondents, 48 people experienced different stress levels whether it is mild, moderate, heavy or severe. In addition, 17 people experienced the tendency of eating disorder. The result of the bivariate analysis showed a significant relationship between stress level and the tendency of eating disorder (p value = 0,001). This study concluded that there is a significant relationship between stress level and the tendency of eating disorder among medical students of Warmadewa University